Archaeometallurgy in Global Perspective: Methods and Synthese - Roberts, Benjamin W.; Thornton, Christopher P. (Springer, 2020)
The study of ancient metals in their social and cultural contexts has been a topic of considerable interest in archaeology and ancient history for decades, partly due to the modern dependence on technology and man-made materials. The formal study of Archaeometallurgy began in the 1970s-1980s, and has seen a recent growth in techniques, data, and theoretical movements,...